Design, Synthesis, and In Silico Study of Two N-Substituted Pyrazinamide Analogs as Potential Antituberculosis Agents - Zulqurnain, Muhammad; Wati, First Ambar; Nurjanah, Ana; Kavin, Layli Adha Nadira; Afifah, Rizqi Nur; Suyatno; Santoso, Mardi (The Journal of Pure and Applied Chemistry Research, 2025)
Tuberculosis (TB) is an infectious yet often overlooked disease that remains a significant global challenge. Pyrazinamide (PZA), a key drug in the first-line TB treatment regimen, is used to reduce the duration of therapy, making it a compound of great interest for further exploration. Two pyrazine-2-carboxamide analogs have been successfully synthesized and reported, followed by an in-silico evaluation of their potency as antituberculosis agents. Yamaguchi reagent was employed as a coupling agent between pyrazine-2-carboxylic acid and corresponding amine, yielding N-(cyclohexylmethyl) pyrazine-2-carboxamide (D) and N-(4-cyclooctyl) pyrazine-2-carboxamide (E) in 60% and 55%, respectively. The molecular docking analysis of compounds (D) and (E) demonstrated lower binding energies (-7.65 and -7.37 kcal/mol, respectively), in comparison with the standard TB drugs, pyrazinamide and isoniazid. Additionally, ADME and pharmacokinetics evaluations revealed that compounds (D) and (E) meet the essential criteria for oral drug candidacy. These findings suggest that the pyrazinamide analogs (D) and (E) hold significant potential as promising antimycobacterial agents for tuberculosis therapy.